Effect of training in SSG on the ability to repeat sprints in young football players - Barba, F.; Argudo Iturriaga, F. M.; Borges-Hernández, P. J.; Ruiz-Lara, E.; Perdomo, A. (Journal of Physical Education and Sport, 2020)
Introduction: Football is one of the most popular team sports worldwide. During a match, players perform varying acyclic activities at differing intensities in order to face the complex and dynamic competition requirements. For this reason, the aim of this study was demonstrate that training in small sided is an effective method for developing the ability to repeat sprints in young football players. Material and Method: Fifty-four male soccer players (U13, U15 and U17, n=18 in which group) at the youth level participated in this study. A program based on Small Sided Games (3vs3) during 6 weeks in a space of 30x25m was applied. A contrast of means, pre and post intervention, was carried out between control and the experimental group and segregating the sample by age group. Results: When analyzing the degree of relationship between RSA fatigue index and jump loss, no significant differences were found. We also studied the relationship between the jump power (CMJ) and the power of the best sprint performed at RSA. Discusion: These results are consistent with those obtained in previous studies (Clemente et al., 2014; Dellal et al., 2012; Owen et al., 2012) on elite players. Conclusion: It can be concluded that this program improves the capacity of recovery before high intensity efforts and allows, at the same time, to work on technical and tactical elements and to develop the physical profile of the players. This type of games provokes improvements in the vertical jump, generate more power in the (CMJ) and the capacity to repeat explosive efforts.Keywords:team sports, speed, jump, motor space, RSA, CM